Impact of Labour Turnover on Organizational Medical Service Delivery - Innocent K Mutatina (Uganda Christian University, 2023)
This research study investigated the effect of employee turnover on organization performance, and how these factors affect the medical service delivery of employees of fort portal referral hospital. The major concern to most organization was that employee turnover is an expensive process especially in organizations that thrives and values viability of the hospital. Lack of Reward management, lack of career growth, lack of health and safety and finally lack of motivation are all factors that contribute to employee turnover. The overall objective of the research project was to determine the effect of employee turnover on Organizational medical service delivery. The project was engaged in descriptive research design as the study was intended to collect quantitative and qualitative data that explained the nature and features of the effect of employee turnover on Organizational medical service delivery. The targeted group for the research study comprised total of 70 employees working at fort portal regional referral hospital. Stratified sampling was used in this research. The targeted population was distributed into three categories namely, Top management staff, middle level management staff and subordinate staff. Primary data was collected using oral interview and structured questionnaires. The collected data was analysed using Microsoft excel and presented in the form of pie charts and tables. Basing on the study findings, the organization needed current strategies for reducing employee turnover rates since the employee reward offered to the employee were not satisfactory, 61% of the employees stated that the organization was not committed to employee career growth development which denied the employees with an opportunity for career growth, the employees stated that low level of motivation influenced the realization of increased employee turnover employee health and safety management which was represented by 77% . The following were the recommendations of the study; that the organization should re-evaluate its employee salary/wages benefits packages to improve the morale and motivation of the employees, the hospital should offer opportunities for career growth, the organization should involve its employees in the decision making processes, the hospital should improve working conditions within the organization finally the organization should apply strategies to reduce employee turnover rate by retaining best employees to improve organizational medical service delivery. The study concluded that lack of reward management, lack of career growth management, lack of health and safety management and lack of motivation management affected negatively to the organizational medical service delivery hence influenced the realization of increased employee turnover.
This is a dissertation .